The Influence of Competence, Training, and Career Development on the Performance Members of Hanudnas Pusdiklat Surabaya - Rizki Anggriawan Saputra; Mohammad Choldum Sina Setyadi; Bambang Supriadi (Trescode Green Organization, 2024)
This research aims to analyze the influence of Competency, training, and career development on the performance of the Surabaya Hanudnas Education and Training Center members simultaneously, partially, or dominantly. Location: This research was conducted at the Hanudnas Surabaya Education and Training Center, Jl. Wiratno, Comp. Kenjeran, District. Bulak, Surabaya, East Java 60121. The type of research used is explanatory research. The population in this study were all students of the Surabaya Hanudnas Education and Training Center, totaling 200 students with a total sample of 135. Data analysis used descriptive analysis techniques and multiple regression analysis to determine the influence of the variables competency, training, and career development on member performance, which will then be continued with hypothesis testing. The research results show that Competency, training, and career development affect the performance of the Surabaya Hanudnas Education and Training Center members, both simultaneously and partially. Furthermore, this research identified that career development has a dominant influence on the performance of the Surabaya Hanudnas Education and Training Center members. The expected contribution from the results of this research can be used as input for practitioners and the Surabaya Hanudnas Education and Training Center so that members' performance will increase. For Pusdikhanudnas Surabaya to further improve the performance of its members, this is done by improving the quality of competence members possess.